Evolución de la recaudación tributaria de impuesto a la renta de tercera categoria en la provincia de Maynas periodo 2020 – 2022 - Flores Ayarza, Diego (2024)
Tax collection is an important aspect in the public finances of every country, in the province of Maynas, there are no research at the university level that has explored the issue of third category income tax collection, despite the importance that This tax has on the local economy and public finances. The present work proposes as a general purpose to determine how the evolution of tax collection of third category income tax is presented in the province of Maynas Period 2020 - 2022, for them a quantitative, observational study and descriptive non-experimental design was developed. that I consider the years 2020 to 2020 as a sample to identify the collection by tax regimes of third category income in the province of Maynas, for which a data collection form was applied, obtaining as main results that the tax collection of the 4 tax regimes present a growing trend in the period, the General Regime contributes 73.08% of the total collected, the Special Income Regime represents 6.72% of the total collection, the Mype Tax Regime contributes 19.54% of the tax revenues and The Simplified Single Regime contributes a small percentage of 0.66% to the total, concluding that the tax collection of third category income tax in the province of Maynas Period 2020 - 2022, presents an evolution with an increasing trend, going from 79,410,735.05 to 151,717,064.49.